The Isolated Brain Microvessel: A Versatile Experimental Model of the Blood-Brain Barrier - Pardridge, William M. (Frontiers in Physiology, 2020)
A versatile experimental model for the investigation of the blood-brain barrier (BBB), including the neuro-vascular unit, is the isolated brain microvessel preparation. Brain microvessels are primarily comprised of endothelial cells, but also include pericytes, pre-capillary arteriolar smooth muscle cells, astrocyte foot processes, and occasional nerve endings. These microvessels can be isolated from brain with a 3 hour procedure, and the microvessels are free of brain parenchyma. Brain microvessels have been isolated from fresh animal brain, fresh human brain obtained at neurosurgery, as well as fresh or frozen autopsy human brain. Brain microvessels are the starting point for isolation of brain microvessel RNA, which then enables the production of BBB cDNA libraries and a genomics analysis of the brain microvasculature. Brain microvessels, combined with quantitative targeted absolute proteomics, allow for the quantitation of specific transporters or receptors expressed at the brain microvasculature. Brain microvessels, combined with specific antibodies and immune labeling of isolated capillaries, allow for the cellular location of proteins expressed within the neuro-vascular unit. Isolated brain microvessels can be used as an “in vitro” preparation of the BBB for the study of the kinetic parameters of BBB carrier-mediated transport (CMT) systems, or for the determination of dissociation constants of peptide binding to BBB receptor-mediated transport (RMT) systems expressed at either the animal or the human BBB. This review will discuss how the isolated brain microvessel model system has advanced our understanding of the organization and functional properties of the BBB, and highlight recent renewed interest in this 50 year old model of the BBB.